THE MEDIATING ROLE OF STRATEGIC ENTREPRENEURSHIP ON CORPORATE ENTREPRENEURSHIP AND FIRM PERFORMANCE OF SMES IN NIGERIA: AN EMPIRICAL STUDY - Ayorinde, Afisat Abolore; Muhd Yusuf, Dayang Hasliza; Abdul Ghani, Mohd Rosli; Jamaluddin , Raziff; Kamaruddin, Nur Syuhadah (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
Corporate entrepreneurship has attracted researchers and executives for its effectiveness in gaining competitive advantage, revitalizing, and improving firms’ performance. However, empirical study investigating the role of strategic entrepreneurship as an intermediary mechanism on the relationship between corporate entrepreneurship and firm performance is yet to be fully explored. Therefore, this study examines the mediating role of strategic entrepreneurship on the link between corporate entrepreneurship dimensions and performance of Small and Medum Enterprises (SMEs) in Nigeria in the South-West geopolitical zone. The study is grounded on three integrated theories, namely, resource-based view, dynamic capabilities theory, and knowledge-based theory. Stratified, proportionate, and simple random technique was used to gather data from a sample of 445 owner managers/chief executive officers (CEOs) of Nigerian SMEs through a structured questionnaire. Partial least squares structural equation modeling (PLS-SEM) SmartPLS 4 software was employed as analytical technique. The findings reveal that all the corporate entrepreneurship dimensions (innovation, corporate venturing, and strategic renewal) have direct positive and significant effect on firm performance of SMEs. More importantly, strategic entrepreneurship partially mediates in the relationship between the dimensions of corporate entrepreneurship and firm performance. This study offers valuable insights to owner managers/CEOs of SMEs to timely align their entrepreneurial initiatives by exploring new opportunities in order to achieve competitive edge in the ever-evolving business landscape and superior performance. Furthermore, the study implications, limitations and suggestions for future studies were discussed.